Comparative analyses of bioactive Mammea coumarins from seven parts of Mammea americana by HPLC-PDA with LC-MS - Yang, Hui; Jiang, Bei; Reynertson, Kurt A; Basile, Margaret J; Kennelly, Edward J (Journal of agricultural and food chemistry, 2006)
Mammea americana L. is tropical plant in the Clusiaceae family that bears edible fruit. Mammea coumarins are isoprenylated derivatives of the lactones of the 2-hydroxy-Z-cinnamic acids that are bioactive and have limited distribution in three Clusiaceae genera. Qualitative and quantitative analyses were performed to determine the distribution of mammea coumarins in the seed nucleus, seed coat, fruit flesh, fruit skin, leaf, stem, and root of M. americana using high-performance liquid chromatography-photodiode array detector (HPLC-PDA) and liquid chromatography-mass spectrometry (LC-MS). Ten major mammea coumarins, mammea E/BD (1), mammea E/BC (2), mammea E/BA (3), mammea E/BB (4), mammea B/BA hydroxycyclo F (5), mammea B/BD (6), mammea B/BC (7), mammea B/BA (8), mammea B/BB (9), and mammea B/BA cyclo F (10), were isolated and identified from the seed nucleus of M. americana and employed as standards. The HPLC-PDA method was validated with respect to sensitivity, linearity, recovery, accuracy, and precision. The total content (w/w %) of the 10 major mammea coumarins in M. americana was determined to be highest in the root (0.75%), followed by the leaf (0.64%), seed nucleus (0.48%), fruit skin (0.11%), stem (0.08%), seed coat (0.02%), and fruit flesh (<0.01%). The leaf and seed nucleus are rich and sustainable natural sources of mammea coumarins. Additionally, the described HPLC-PDA and LC-MS methods are sensitive and accurate and can be applied to the analysis of mammea coumarins in other samples.